Neuroimaging studies on familiarity of music in children with autism spectrum disorder - De Barros Freitas, Carina Patrícia (2020)
The field of music neuroscience allows us to use music to investigate human cognition in vivo. Examining how brain processes familiar and unfamiliar music can elucidate underlying neural mechanisms of several cognitive processes. To date, familiarity in music listening and its neural correlates in typical adults have been investigated using a variety of neuroimaging techniques, yet the results are inconsistent. In addition, these correlates and respective functional connectivity related to music familiarity in typically developing (TD) children and children with autism spectrum disorder (ASD) are unknown. The present work consists of two studies. The first one reviews and qualitatively synthesizes relevant literature on the neural correlates of music familiarity, in healthy adult populations, using different neuroimaging methods. Then it estimates the brain areas most active when listening to familiar and unfamiliar musical excerpts using a coordinate-based meta-analyses technique of neuroimaging data. We established that motor brain structures were consistently active during familiar music listening. The activation of these motor-related areas could reflect audio-motor synchronization to elements of the music, such as rhythm and melody, so that one can tap, dance and “covert” sing along with a known song. Results from this research guided our second study. This work investigated the familiarity effect in music listening in both TD and ASD children, using magnetoencephalography (MEG). This technique enabled us to study brain connectivity and characterize the networks and frequency bands involved while listening to familiar and unfamiliar songs. TD children recruited a similar brain network as those in typical adults during familiar music listening, in the gamma frequency band. Compared to TD, children with ASD showed relatively intact processing of familiar songs but atypical processing of unfamiliar songs in theta and beta-bands. Atypical functional connectivity of other unfamiliar stimuli has been reported in ASD. Our findings reinforced that processing novelty is a challenge. Overall, this work contributes to the advancement of both fields of music neuroscience and brain connectivity in ASD.